Curbing discriminating human resource practices: A~microfounded perspective - Jennifer Kunz; Laura Michele Ludwig (Schmalenbach Journal of Business Research (SBUR), 2022)
Discrimination constitutes a~sticky phenomenon in corporations despite decades of anti-discrimination initiatives. We argue that this stickiness is related to the complex relations between various factors on the micro level in organizations, which determine and stabilize each other. Based on a~systematic literature review comprising empirical studies on discrimination due to age, gender, race, and ethnicity/nationality, we find eight general mechanisms which can be further clustered into an economic, a~behavioral, and a~socio-structural domain. While mechanisms in the behavioral domain form the roots of discrimination, the economic and the socio-structural mechanisms stabilize each other as well as the behavioral ones. Thus, the analysis shows that the various building blocks on the micro level are entangled with each other and suggests a~structured way by identifying a~problem hierarchy to manage this complexity.
Keywords: 650; Discrimination; Diversity; Human resource practices; Micro-level